2006
DOI: 10.1214/009117905000000602
|View full text |Cite
|
Sign up to set email alerts
|

Dynamical stability of percolation for some interacting particle systems and ɛ-movability

Abstract: In this paper we will investigate dynamic stability of percolation for the stochastic Ising model and the contact process. We also introduce the notion of downward and upward ε-movability which will be a key tool for our analysis.[15] was whether there could exist atypical times at which the percolation structure looks different than at a fixed time.We record here some of the results from [15]; (i) for any graph

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
18
0

Year Published

2006
2006
2011
2011

Publication Types

Select...
4
3

Relationship

3
4

Authors

Journals

citations
Cited by 12 publications
(20 citation statements)
references
References 23 publications
2
18
0
Order By: Relevance
“…Here, |z| denotes the distance to 0, which is the apex of the cone C θ . One can prove that 6) in the very same way that we have justified (7.1). By Theorem 8.1 (and easy algebraic manipulation), it therefore suffices to prove that…”
Section: Upper Bounds For K-arm Timessupporting
confidence: 75%
See 1 more Smart Citation
“…Here, |z| denotes the distance to 0, which is the apex of the cone C θ . One can prove that 6) in the very same way that we have justified (7.1). By Theorem 8.1 (and easy algebraic manipulation), it therefore suffices to prove that…”
Section: Upper Bounds For K-arm Timessupporting
confidence: 75%
“…Next, analogous questions for the Boolean model where the points undergo independent Brownian motions was studied in [5]. Analogous questions for the lattice case for certain interacting particle systems (where updates are not done in an independent fashion) are studied in [6]. Finally in [3], it is shown that there are exceptional two dimensionl slices for the Boolean model in four dimensions.…”
Section: Theorem 13 Almost Surely the Set Of Times T ∈ [0 1] Suchmentioning
confidence: 99%
“…6. The analogous state ments for critical percolati on in cones and wedges a lso holds, with similar proofs.…”
Section: )supporting
confidence: 57%
“…where the inequality comes from the unconditioned version of (5). Taking N = T , we see that (14), (15) cannot hold for all N, T .…”
Section: The One Dimensional Contact Processmentioning
confidence: 95%